Experimental studies of the influence of mobile fan positioning parameters on the ability to transport the air stream into the door opening - Piotr Kaczmarzyk; Łukasz Warguła; Paweł Janik (Scientific Reports, 2023)
Abstract The article aims to determine the influence of fan positioning parameters, i.e., its distance from a door opening (1–7 m) and the angle of inclination of the impeller axis in relation to the ground (0°–18°) on the amount of air flow pumped through a door opening. The experiment was carried out using a mock-up simulating a door opening, on which a measurement plane was located, without the cubic capacity (building structure) behind the door opening. The volumetric air flow stream was determined based on measuring (at 50 measuring points) the velocity of the air stream blown onto the surface of the door opening mock-up. Four commercial positive pressure ventilators, commonly used in rescue operations, with a power of 0.6–6.3 kW were tested. The tests showed that the value of the air flow stream at the most favourable setting (distance in the range of 3–5 m and the angle of the impeller axis to the ground in the range of 5°–12.2°) is included in the range of 18,304 ± 2460 m3/h to about 45,189 ± 4619 m3/h. Such settings cause the air stream to be aimed at the central area of the door opening. Imprecise mobile fan arrangement may reduce the flow rate from 41 to 76% in relation to the most favourable results.